Validation of distinct pathogenic patterns in a cohort of membranoproliferative glomerulonephritis patients by cluster analysis - Garam, Nóra; Prohászka, Zoltán; Szilágyi, Ágnes; Aigner, Christof; Schmidt, Alice; Gaggl, Martina; Sunder-Plassmann, Gere; Bajcsi, Dóra; Brunner, Jürgen; Dumfarth, Alexandra; Cejka, Daniel; Flaschberger, Stefan; et al. (Clinical Kidney Journal, 2020)
BackgroundA novel data-driven cluster analysis identified distinct pathogenic patterns in C3-glomerulopathies and immune complex-mediated membranoproliferative glomerulonephritis. Our aim was to replicate these observations in an independent cohort and elucidate disease pathophysiology with detailed analysis of functional complement markers.MethodsA total of 92 patients with clinical, histological, complement and genetic data were involved in the study, and hierarchical cluster analysis was done by Ward method, where four clusters were generated.ResultsHigh levels of sC5b-9 (soluble membrane attack complex), low serum C3 levels and young age at onset (13 years) were characteristic for Cluster 1 with a high prevalence of likely pathogenic variations (LPVs) and C3 nephritic factor, whereas for Cluster 2—which is not reliable because of the small number of cases—strong immunoglobulin G staining, low C3 levels and high prevalence of nephritic syndrome at disease onset were observed. Low plasma sC5b-9 levels, decreased C3 levels and high prevalence of LPV and sclerotic glomeruli were present in Cluster 3, and patients with late onset of the disease (median: 39.5 years) and near-normal C3 levels in Cluster 4. A significant difference was observed in the incidence of end-stage renal disease during follow-up between the different clusters. Patients in Clusters 3–4 had worse renal survival than patients in Clusters 1–2.ConclusionsOur results confirm the main findings of the original cluster analysis and indicate that the observed, distinct pathogenic patterns are replicated in our cohort. Further investigations are necessary to analyse the distinct biological and pathogenic processes in these patient groups.